Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/add.13271
|View full text |Cite
|
Sign up to set email alerts
|

What should national alcohol control policies in Muslim majority countries focus on?

Abstract: Commentary to: http://onlinelibrary.wiley.com/doi/10.1111/add.13159/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Most intoxicated drivers reported that drinking did not interfere with their performance but reported the opposite answer after intervention (follow-up period). The decision to drive or not after using alcohol depends on a previous intention that is affected by the self-criticism of drivers concerning the risk involved in this behavior, which might be altered when they are under the effect of alcohol (20) . In the current study, all drivers were alerted about the risk involved in drinking and driving and how little knowledge on traffic laws and they do not think penalties will be applied to them (9,14) .…”
Section: Discussionmentioning
confidence: 99%
“…Most intoxicated drivers reported that drinking did not interfere with their performance but reported the opposite answer after intervention (follow-up period). The decision to drive or not after using alcohol depends on a previous intention that is affected by the self-criticism of drivers concerning the risk involved in this behavior, which might be altered when they are under the effect of alcohol (20) . In the current study, all drivers were alerted about the risk involved in drinking and driving and how little knowledge on traffic laws and they do not think penalties will be applied to them (9,14) .…”
Section: Discussionmentioning
confidence: 99%
“…Assanangkornchai and colleagues further emphasize the role of the global alcohol market in increasing alcohol consumption in MMCs, especially its effect on youth via social media, internet and user‐generated content such as Facebook and Twitter. Indeed Bahelah notes that alcohol policy development should specifically target youth alcohol consumption.…”
mentioning
confidence: 99%
“…Refusal to provide consent by parents or assent by participants, dual use of waterpipe and cigarettes, and not intending to initiate smoking were exclusion criteria. More details about the WDLY study can be found elsewhere (Bahelah et al, 2016).…”
Section: Participantsmentioning
confidence: 99%